The Role of Artificial Intelligence in Enhancing Human Longevity: Mitigating Cognitive Overload for Extended Lifespan Among Master's Students in Mathematics at the Catholic University of Ghana - Addae, Richmond Kakra; Brown, Cecilia (Golden Ratio of Social Science and Education, 2025)
This article studied the influence of artificial intelligence on alleviating cognitive load and promoting cognitive longevity in master's mathematics students at the Catholic University of Ghana. Stress in academic programs, time constraints, and burnout are rising issues, particularly in postgraduate programs in STEM. Therefore, this study examines the impact of AI apps such as ChatGPT, WolframAlpha, and Grammarly on providing cognitive support and emotional sustenance in academic environments. The study is guided by Cognitive Load Theory (Sweller, 1988), Allostatic Load Theory (McEwen, 1998), and Socio-Technical Systems Theory (Trist, 1981) and follows a mixed-method approach consisting of survey data from 100 master's students and in-depth interviews. The survey revealed that 78 percent were moderately to highly cognitively overloaded, while 65 percent utilized AI to work on their academic tasks. A notable negative relationship was found between AI use and perceived stress (r = -0.42, p < 0.01), with more confidence in academic work and improved time management. ANOVA revealed significant differences in stress levels among the different frequencies of AI use (F = 4.56, p < 0.05). Qualitative analyses generated the core themes of "AI as a cognitive assistant," "digital dependency," and "emotional assurance." Their reports indicated that they used AI to help them understand complex mathematical ideas, organize their academic writing, and calm their nerves about presentations. However, they voiced worries about becoming overdependent on it, issues of academic integrity, and ethics concerning AI's role in learning. The end product maintains that AI is a reasonable tool for easing cognitive load, encouraging mental well-being, and enhancing cognitive longevity. These findings have policy implications for the inclusion of AI literacy in both academic and national digital educational frameworks. AI implementation strategies could disappear into the topping of teaching success while serving the broader public health agenda of student mental health and human capital development.